Control Strategy of Interleaved Buck Converter for Automated Guided Vehicles with Misalignment in Wireless Power Transfer Systems - Suwaphit Phongsawat; Worapong Pairindra; Surin Khomfoi; Teeraphon Phophongviwat; Noureddine Takorabet; Phatiphat Thounthong (My University, 2024)
The analysis of the positioning of the power transmission coil with a power rating of 3 kW and an output voltage of 48 V at a frequency of 85 kHz is presented, along with a simulation of the wireless power transfer (WPT) control system using an LCC-S resonance compensation circuit, applied to automated guided vehicles (AGVs). The case where the coil positions are misaligned with a deviation of 0–20% from the size of the power transmission coil is considered. Apparently, it can be illustrated that when the two power transmission coils are misaligned, the battery can still be charged in constant current mode using an interleaved buck converter circuit through a PI controller to increase the output power. The operation is simulated using MATLAB/Simulink software.
Keywords: Wireless Power Transfer Systems